The Design and Development of Oven Using Dissipative Heat from Refrigerator - Suhaimi, Misha; Md Daud, Nazri; Wasbari, Faizil; Herawan, Safarudin Gazali (2011)
Refrigerators have been used since long time ago to preserve perishable foods. Nowadays it becomes one of the essential appliances in a household. Today’s refrigerators use much less energy as a result of using smaller and higher efficiency motors and compressors, better insulation materials, larger coil surface areas and better door seals. However, the basic vapour- compression refrigeration cycle has remained unchanged. The condenser coil at the back of the refrigerator dissipates heat to the surrounding. As long as the refrigerator is on, the condenser coil will continuously dissipate heat to the surrounding air. This project is to utilize the heat from condenser to warm the oven compartment. The condenser coil is modified to enter oven compartment before return back to existing coil. The temperature distribution from the condenser to oven compartment was investigated through experiment. The analysis of the refrigerator performance is also done to study the effect of modification to the refrigerator. The heat can be used to develop low temperature oven at the top of the refrigerator. The oven is not required any electrical heater. The results show that the heat is capable to warm the oven compartment more than 63°C. However, the electricity consumption increases because the compressor has to work hard to force the refrigerant flow in the longer condenser coil. There are still a lot of improvements need to be done in order to improve the oven and refrigerator performance.